Broomeanamides: Cyclic Octapeptides from an Isolate of the Fungicolous Ascomycete Sphaerostilbella broomeana from India - Ekanayake, Dulamini I. (J Nat Prod, 2021)
[Image: see text] The genus Sphaerostilbella comprises fungi that colonize basidiomata of wood-inhabiting fungi, including important forest pathogens. Studies of fermentation cultures of an isolate (TFC201724) collected on the foothills of Himalayas, and closely related to S. broomeana isolates from Europe, led to the identification of a new cyclic octapeptide along with two closely related analogues (1–3) and four dioxopiperazines (4–7). The structure of the lead compound, broomeanamide A (1), was assigned mainly by analysis of 2D NMR and HRESIMS data. The structure consisted of one unit each of N-MeVal, Ala, N-MePhe, Pro, Val, and Ile and two N-MeLeu units. The amino acid sequence was determined on the basis of 2D NMR and HRESIMSMS data. NMR and HRMS data revealed that the other two new peptides have the same amino acid composition except that the Ile unit was replaced with Val in one instance (2) and the N-MeVal unit was replaced with Val in the other (3). The absolute configuration of 1 was assigned by analysis of the acid hydrolysate by application of Marfey’s method using both C(18) and C(3) bonded-phase columns. Broomeanamide A (1) showed antifungal activity against Cryptococcus neoformans and Candida albicans, with MIC values of 8.0 and 64 μg/mL, respectively.